Manajemen Filantropi - Mohammad Ridwan; Cicih Maryati; Dhea Silviana Latifah; Feby Juan Hendarwan; Dwiki Muhammad Fadhillah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Islamic philanthropy management plays an important role in managing zakat, infaq, alms and waqf funds in a structured and accountable manner. The aim is to achieve social justice and equal distribution of welfare, help the poor, support social development, and strengthen the Islamic brotherhood. The basic principles of Islamic philanthropy management include sincerity, justice, target accuracy, efficiency and accountability. In its implementation, professional philanthropic institutions are established, effective fund collection systems, use of information technology, development of human resources, and development of innovative philanthropy programs. With effective management of Islamic philanthropy, it is hoped that it can create a just, prosperous and noble society.